A Self Made of Words : Crafting a Distinctive Persona in Nonfiction Writing - Klaus, Carl H. (Book collections on Project MUSE., 2013)
Confident or fretful, solemn or sassy, tough or tender, casual or formal: the self you project in writing - your persona - is the byproduct of numerous decisions you make about what to say and how to say it. Though any single word or phrase or sentence might make little difference within the scope of an entire essay or book, collectively they create an impression of who you are or seem to be - an impression that's sure to influence how readers respond to your work. Thus it's essential to take charge of how you come across on the page, to craft an appropriate persona for whatever you're writing. This book shows how to adapt your self to the needs of various forms of nonfiction writing.